Upaya Pencegahan Stunting Terhadap Masyarakat di Desa Tumpang Kecamatan Tumpang Kabupaten Malang Jawa Timur - Annisa Uttahira; Marsha Nabila; Chintaku Fadillah; Puji Endah Purnamasari (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2024)
This journal discusses the serious problem of stunting in Tumpang Village, Malang Regency. The main focus is on prevention strategies, including health education, distribution of additional food for pregnant women and toddlers, and promotion of early marriage. This study used a descriptive qualitative method, namely by involving the local community, including educational programs aimed at parents of toddlers and pregnant women. The results obtained are increasing community insight regarding how to prevent stunting, one of which is by improving sanitation and avoiding early marriage.